A study of hypoglycemic effect of Caesalpinia bonduc extract on alloxan induced diabetic albino rats - Nadaf, Reshma (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The objective of the study was to scientifically investigate the oral hypoglycemic activity of Caesalpinia bonduc on Alloxan induced diabetic albino rats. To compare the hypoglycemic effect of Caesalpinia bonduc with that of the standard drug Glibenclamide used in the treatment of diabetes mellitus. Methods: Adult healthy albino rats of wister strain of either sex weighing 150-200gms were included in the study. The animals were divided into 4 groups namely control, diabetic control, standard and test groups with 6 animals in each group. Diabetes was chemically induced using alloxan to produce hyperglycemia in rats. Standard drug Glibenclamide suspended in gum acacia was administered for standard group. Test drug Caesalpinia bonduc was administered for test group. Morning around 9 a.m. blood glucose levels were recorded on 1st, 3rd, 7th, 14th, 21st, and 28th days. Results: The control group of rats showed no variation. The diabetic control rats showed consistent hyperglycemia. Comparing the test drug Caesalpinia bonduc to the standard drug Glibenclamide, the test drug was 1.38 times more efficacious than the standard. Conclusions: The alcoholic extract of Caesalpinia bonduc (seeds) has shown more anti diabetic activity by lowering the blood glucose levels in diabetic rats significantly. These findings suggest that hypoglycemic potential of the test compound Caesalpinia bonduc is promising and found to be more significant than the standard compound.